Functional Gene Polymorphisms in Aggressive and Chronic Periodontitis - Brett, P.M.; Zygogianni, P.; Griffiths, G.S.; Tomaz, M.; Parkar, M.; D’Aiuto, F.; Tonetti, M. (Journal of dental research, 2005)
There is strong evidence that genetic as well as environmental factors affect the development of periodontitis, and some suggestion that aggressive and chronic forms of the disease share the same genetic predisposition. This study addresses the hypothesis that there are both shared and unique genetic associations in these forms of periodontitis. A sample of 51 patients with aggressive disease, 57 patients with chronic disease, and 100 healthy controls was recruited for this study. Ten functional polymorphisms in 7 candidate genes were genotyped. The results show statistically significant (p ≤ 0.05) differences between genotype frequencies in aggressive and controls (IL-1B +3954 & IL-6 −174); chronic and controls (IL-6 −174 & VDR −1056); chronic and aggressive periodontitis (IL-1A −889); and periodontitis as a whole and controls (VDR −1056, TLR-4 399 & IL-6 −174). These results suggest that there are in fact both shared and unique genetic associations in aggressive and chronic periodontitis.